The effect of stocking density on sterlet Acipenser ruthenus (Linnaeus, 1758) larvae in the recirculating aquaculture system. (27th June 2022) - Fazekas, Georgina; Káldy, Jenő; Kovács, Gyula; Müller, Tamás; Ljubobratović, Uroš
Abstract: Increasing the number of fish stocked might optimize the efficiency of intensive aquaculture systems however at the same time might have a negative impact on fish welfare and growth parameters. In the current study, three different stocking densities were evaluated in duplicated tanks to investigate the effect of different stocking densities on the survival and growth of sterlet larvae from hatching until the end of weaning, during the 30‐day trial. Tested densities were 5, 10, and 20 larvae L −1 in the low (L), medium (M), and high (H) density group, respectively. Freshly hatched larvae (1250, 2500, 5000 larvae per duplicated tanks) were divided into three treatment groups in 250 L raceway larval rearing tanks. The fish biomass gain was significantly higher in each group of higher stocking densities (0.2 ± 0.0 g L −1 ; 0.4 ± 0.0 g L −1 and 0.8 ± 0.1 g L −1 respectively, r  = .990, p  < .001). The L group showed a tendency towards better growth during the first 3 weeks, however, at the end of the trial, no significant differences were observed. The highest mortality at the start of exogenous feeding was noticed in group H (12.77% ± 1.3%) and was significantly different from the two lower density groups (5.16% ± 1.3% in L, 7.94% ± 1.3% in M), however, the overall mortality at the end of the trial did not differ among groups. Results on both growth and mortality during the later periods are suggesting the adaptability of sterlet larvae to the more intensive rearing conditions. Thus, it can be stated that the application of a stocking density of 20 larvae L −1 is appropriate in the initial period of larval rearing in the sterlet.